Assessing the Incidence of Symptomatic Respiratory Syncytial Virus Illness Within a Prospective Birth Cohort in Managua, Nicaragua. (29th July 2019) - Kubale, John; Kuan, Guillermina; Gresh, Lionel; Ojeda, Sergio; Azziz-Baumgartner, Eduardo; Sanchez, Nery; Lopez, Roger; Harris, Eva; Balmaseda, Angel; Gordon, Aubree
Abstract: Background: Respiratory syncytial virus (RSV) causes substantial morbidity and mortality among children worldwide, commonly through acute lower respiratory tract infections (ALRI). To assess the incidence rate of symptomatic RSV illness among young children, we conducted a prospective birth cohort study following children from 0–2 years of age in Managua, Nicaragua. Methods: Children meeting the testing criteria (fever, history of fever, or severe respiratory symptoms [apnea, stridor, nasal flaring, wheezing, chest indrawing, and/or central cyanosis]) were tested for RSV infections using real-time reverse transcriptase-polymerase chain reaction. An acute lower respiratory infection was defined as a diagnosis of pneumonia, bronchiolitis, bronchitis, or bronchial hyperreactivity. The incidence rate was calculated, and 95% confidence intervals were estimated using a Poisson distribution. Results: A total of 833 children participated in the cohort: 289 (34.7%) had at least 1 episode of laboratory-confirmed RSV, and 156 (18.7%) of had an episode of RSV-associated ALRI (RSV-ALRI). The incidence rate of symptomatic RSV was 248.1 cases per 1000 person-years (95% confidence interval [CI] 223.2–275.7). While infants aged 6–11 months had the highest incidence of symptomatic RSV (361.3/1000 person-years, 95% CI 304.4–428.8), infants <3 months had the highest incidence of severe RSV (RSV-associated hospitalizations and/or severe ALRI). RSV was also associated with 25.0–37.5% of deaths from medical causes (n = 8). Conclusions: A substantial burden of RSV exists among children aged <2 years in Nicaraguan communities. RSV was also a leading cause of infant mortality among study participants. The development and implementation of effective RSV prevention and treatment measures represent an opportunity to substantially reduce severe illness and death among children worldwide. Abstract : Around one-third of medical deaths among Nicaraguan children under 2 years were respiratory syncytial virus–associated, suggesting it's an important driver of infant mortality in highly vaccinated populations with little human immunodeficiency virus or malaria.